Կիլիկյան Հայաստանի Ձորովանքը և գրչական ժառանգությունը - Բադալյան, Հասմիկ (Մատենադարան)
The article is devoted to the history of the Dzorovank monastery, one of the spiritual and cultural regional centers of Cilician Armenia in the 13th-14th centuries, and to the activities of the monastery scribes, miniaturists, and members of the congregation. The historical and philological research for the assessment of the scriptorium’s heritage is based on the catalogs of Armenian manuscripts and the manuscript sources of Matenadaran, Mesrop Mashtots‘ Institute of Ancient Manuscripts. For the first time, 11 manuscripts (only 6 were previously known) from the Dzorovank‘ monastery have been studied and brought to scholars’ attention. The names of scribes and miniaturists are listed, as well as their activities and the circumstances of copying those manuscripts are discussed. Статья посвящена истории монастыря Дзорованк, одного из духовно-культурных региональных центров Киликийской Армении XIII-XIV веков, деятельности монастырских писцов, миниатюристов и членов конгрегации. Историко-филологическое исследование основано на рукописных источниках Матенадарана имени Маштоца и каталогах армянских рукописей. Впервые были введены в научный оборот 11 рукописей из монастыря Дзорованк (ранее были известны 6 рукописей). Выявлены имена писцов и миниатюристов, результаты их деятельности, обстоятельства копирование ими рукописей.
Keywords: Բանասիրություն